On the precision of full-spectrum fitting of simple stellar populations. IV. A systematic comparison with results from colour-magnitude diagrams - Asa'd, Randa (2022)
In this fourth paper of a series on the precision of ages of stellar populations obtained through the full-spectrum fitting technique, we present a first systematic analysis that compare the age, metallicity and reddening of star clusters obtained from resolved and unresolved data (namely colour-magnitude diagrams (CMDs) and integrated-light spectroscopy) using the same sets of isochrones. We investigate the results obtained with both Padova isochrones and MIST isochrones. We find that there generally is a good agreement between the ages derived from CMDs and integrated spectra. However, for metallicity and reddening, the agreement between results from analyses of CMD and integrated spectra is significantly worse. Our results also show that the ages derived with Padova isochrones match those derived using MIST isochrones, both with the full spectrum fitting technique and the CMD fitting method. However, the metallicity derived using Padova isochrones does not match that derived using MIST isochrones using the CMD method. We examine the ability of the full-spectrum fitting technique in detecting age spreads in clusters that feature the extended Main Sequence Turn Off (eMSTO) phenomenon using two-population fits. We find that 3 out of 5 eMSTO clusters in our sample are best fit with one single age, suggesting that eMSTOs do not necessarily translate to detectable age spreads in integrated-light studies.